‘Self-Image’ Features in Gifted Senior Preschoolers - Elena S. Belova (RUDN Journal of Psychology and Pedagogics)
The article is devoted to one of the topical problems of modern psychology - the development of self-awareness in children - as it is considered in the psychology of giftedness. The study was aimed at identifying ‘self-image’ features in creatively gifted senior preschool children. It was carried out in line with the scientific approach proposed by A.M. Matyushkin to the study of giftedness as a prerequisite for the development of a creative personality. The study involved 290 children aged 6-7 years ( M = 6.6; SD = 0.54; boys = 143, girls = 147) attending preschool educational institutions in Moscow. The creative potential of the participants (senior preschool children) was identified using Figural Form A of the Torrance Tests of Creative Thinking (TTCT), as well as on the basis of observations, surveys of teachers and parents, and expert assessments of the children’s creative works. The results made it possible to identify a group of gifted senior preschoolers with high creative potential ( N = 52, boys = 26, girls = 26) and a group of their peers, equal in quantitative composition and gender distribution, whose creative potential was lower. The child’s ‘self-image’ features were revealed during a conversation based on the Twenty Statements Test - TST (M. Kuhn and Th. McPartland, modified by T.V. Rumyantseva) and the Study of the System of Children’s Self-Characteristics (O.A. Belobrykina). The analysis of the obtained data showed the relationship between the results of the Torrance Test performed by the senior preschoolers and the number of their self-characteristics. The following differences between the groups were highlighted: the gifted children named more characteristics when describing themselves than their peers; this was especially true for such subcategories of answers as ‘gender’, ‘age’, ‘role in society’, ‘role in the family’, ‘physical qualities’, ‘communication’, ‘abilities’, and ‘general’. The analysis of the ‘self-image’ structural components revealed that the group of the gifted children, to a greater extent than the group of their peers, represented the indicators of the social, communicative, physical, active and reflexive components. All this indicates a greater volume and greater degree of cognitive complexity and differentiation of the ‘self-image’ in the gifted senior preschoolers compared to their peers. At the same time, the following ‘self-image’ aspects common to both groups were identified: the predominance of self-characteristics of the subjective category (personality traits, skills, etc.) and emotionally positive responses. A comparison of the ‘self-images’ between the gifted boys and gifted girls showed that the girls had more pronounced ‘emotional characteristics (cheerful)’, ‘description of appearance (beautiful)’ and ‘role in the family’. The results obtained can be used in creating programs aimed at the emotional and personal development of gifted preschoolers, as well as in the process of consultative work on the prevention/correction of difficulties in the upbringing of preschoolers.